Practical Lecture: Best Practices for Effective Teaching Using the Star Method for Class Leaders - Mclean HY; Adi Isma; Amrang Amrang; Ahmad Junaedi; Dwi Adi Nugroho; Asdar Asdar (PT. Global Research Collaboration, 2025)
In the momentum of the 2035 Demographic Bonus and the vision of Golden Indonesia 2045, there are both challenges and great opportunities for Indonesia's education system, where students are required to have soft skills, character, and critical thinking abilities. To realize this, Practitioner Lectures serve as a tangible form of practice in building teaching competence by connecting theory with direct experience from the professional or working world. This article describes the implementation of a national webinar titled “Practical Lecture: Building Teaching Competence Through Real Practice,” organized by the English Education Study Program, West Sulawesi University. This Practitioner Lecture aims to train students to become class leaders and to carry out best teaching practices using the STAR Method (Situation, Task, Action, Result). The activity was held online via the Zoom Meeting platform on August 13, 2025, featuring experienced speakers in the field of education. A total of 69 participants attended and stayed until the end of the event. The event evaluation was conducted through an online form, covering satisfaction with the material, presenters’ delivery, and relevance to participants’ academic needs. Evaluation results proved that the implementation of the practitioner lecture in building teaching competence was very successful, with the majority of participants stating a combination of engaging and easy-to-understand material, good and interactive delivery, as well as opportunities to gain valuable insights and real experience for the development of teaching skills and the professional growth of future teachers. Through this training, participants will gain a deep understanding of teaching techniques that not only emphasize material delivery but also classroom management and increasing student engagement. The expected outcome is the creation of class leaders capable of managing learning more effectively and inspiringly, supporting the achievement of optimal educational goals.